The Clock Counts – Length Effects in English Dyslexic Readers - Provazza, S.; Giofrè, D.; Adams, A.-M.; Roberts, D. J. (Frontiers in Psychology, 2019)
In reading, length effects (LEs) are defined as an increment in the time taken to read as a function of word length and may indicate whether reading is proceeding in an efficient whole word fashion or by serial letter processing. LEs are generally considered to be a pathognomonic symptom of developmental dyslexia (DD) and predominantly have been investigated in transparent orthographies where reading impairment is characterized as slow and effortful. In the present study a sample of 18 adult participants with DD were compared to a matched sample of typical developing readers to investigate whether the LE is a critical aspect of DD in an opaque orthography, English. We expected that the DD group would present with marked LEs, in both words and non-words, compared to typical developing readers. The presence of LEs in the DD group confirmed our prediction. These effects were particularly strong in low frequency words and in non-words, as observed in reading speed. These preliminary findings may have important theoretical implications for current understanding of DD.